Community Needs Assessment in Sitio Sapa, Barangay San Rafael, Rodriguez, Rizal: Basis of Social Welfare Extension Program of the University of Rizal System Rodriguez, Rizal - Ma. Victoria H. Alarte (Asean Social Work Journal, 2022)
The incorporation of community services about the need for a sustainable livelihood program was evaluated in this report. The four hundred (400) residents were taken as respondents, using full household enumeration. Most of the respondents in Rodriguez Rizal are purely uplifted and hailed, living a simple modern way of life brought about by industrialization in the region. However, considering the number of years they live in the area, they still have limited earnings due to limited educational qualifications. Most of the family's meager income is spent on their food. Therefore, poverty is always felt among them, so the need for a sustainable livelihood program that is important, productive, and beneficial is required to achieve a fulfilling and meaningful existence. The government provides limited economic and social infrastructure. The results demonstrate that there is a need for a program to enhance their living conditions. It is recommended that in partnership with the local government unit and the school, steps should be taken to improve the community's livelihood by expanding appropriate research-based community services. The following advice was proposed in response to the analysis carried out and from the data collected. A partnership between the Barangay Unit and the Local Government Unit is primarily via the Municipal Office for Social Welfare and Development and the Social Work and Community Development College. A Sitio Sapa Community mobilization operations such as capacity building enable them to be self-confident through the social security program. Through social growth, an extension program links the needs and resources of the Community to the residents of Sitio Sapa as part of the dual objective of the Conditional Cash Transfer being implemented in the region. Through investment in human resources (i.e., education, health, and nutrition), social development breaks the cycle of poverty. To address the capacities of the citizens in the region, a social welfare program will be planned.